2015
DOI: 10.1007/s11999-014-4007-x
|View full text |Cite
|
Sign up to set email alerts
|

Injury Risk to Extraosseous Knee Vasculature During Osteotomies: A Cadaveric Study With CT and Dissection Analysis

Abstract: Background Realignment osteotomies about the knee may be performed as distal femoral or proximal tibial osteotomies; both may be performed either on the medial or lateral sides of the knee, in closing-or opening-wedge fashion. Although rare, injury to neurovascular structures may occur, and the proximity of the vascular structures to the osteotomy saw cuts has been incompletely characterized. Questions/purposes We performed a cadaver study to assess the risk of vascular injury in patients undergoing realignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 27 publications
(53 reference statements)
0
34
0
2
Order By: Relevance
“…More studies, similar to those of Bisicchia et al [3] and others investigating the blood supply around the knee [10,12,18], are required to expand our knowledge on the patterns and distribution of blood supply in these regions. Such studies have the capacity to create a representative database, which may then facilitate improvements in the surgical techniques for knee osteotomies, enhance osteotomy and wound healing and reduce complications.…”
Section: How Do We Get There?mentioning
confidence: 84%
See 2 more Smart Citations
“…More studies, similar to those of Bisicchia et al [3] and others investigating the blood supply around the knee [10,12,18], are required to expand our knowledge on the patterns and distribution of blood supply in these regions. Such studies have the capacity to create a representative database, which may then facilitate improvements in the surgical techniques for knee osteotomies, enhance osteotomy and wound healing and reduce complications.…”
Section: How Do We Get There?mentioning
confidence: 84%
“…Bisicchia et al [3] investigated the extraosseous blood supply of the knee and assessed the risk of damage to these vessels during DFO and PTO. They showed that, in every one of the 12 osteotomies investigated, one or more arteries were at risk.…”
Section: Where Do We Need To Go?mentioning
confidence: 99%
See 1 more Smart Citation
“…Osteotomies may cause bleeding complications not only as periosteal vessels are cut in the trajectory of the osteotomy bone cuts, but also when larger vessels near to the bone are not protected. Previous conducted cadaveric studies mainly have focused on high tibial osteotomy and the associated risk to the larger vessels (Darnis et al 2014 ; Kim et al 2010 ; Bisicchia et al 2015 ; Tindall et al 2006 ; Georgoulis et al 1999 ; Ebraheim et al 1998 ). With respect to the medial side of the distal femur, the vascular anatomy has been studied in the midvastus approach in total knee replacement surgery (Başarir et al 2006 ; Scheibel et al 2002 ).…”
Section: Introductionmentioning
confidence: 99%
“…Specific literature on the vascular anatomy related to distal femoral osteotomies is scarce (Visser et al 2013 ; Bisicchia et al 2015 ). Visser et al ( 2013 ) described a less invasive approach to the distal medial aspect of the femur in biplanar medial closed-wedge distal femoral osteotomy, which proved to be feasible and safe.…”
Section: Introductionmentioning
confidence: 99%